DEVELOPING A MODEL FOR WASTE MANAGEMENT AND POLLUTION PREVENTION IN NAVAL ENGINEERING OPERATIONS AT POLTEKPEL SULUT - Anwar, Dedtri; Alamsyah, Jaya; Setiawan, Hadi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Background: Waste management and pollution prevention in naval engineering operations are critical to minimizing environmental damage and ensuring regulatory compliance. The Sulawesi Sea’s fragile ecosystem and maritime sustainability goals necessitate an effective and structured waste management framework for naval institutions. Despite the existence of environmental regulations, challenges persist in compliance enforcement, cadet training, and operational waste disposal efficiency. Original Value: This research contributes to naval environmental sustainability by developing a structured waste management model tailored to naval engineering training institutions. Unlike previous studies that focus on commercial shipping waste, this study provides a specific analysis of waste generation in naval engineering settings and offers targeted improvements for pollution prevention. Objectives: The study addresses how an optimized waste management and pollution prevention model can improve environmental sustainability in naval engineering operations, while also identifying training gaps and regulatory compliance challenges. Methodology: The research employs qualitative analysis through expert interviews, field observations, and structured surveys to evaluate current waste management effectiveness, regulatory adherence, and cadet engagement. Results: Findings indicate that waste segregation and pollution prevention measures are effective (88-92/100), but regulatory enforcement and hands-on cadet training require improvement (85/100). The proposed model is feasible (87/100) and cost-effective (89/100), ensuring long-term operational sustainability. Conclusions: Implementing structured waste policies, enhanced training modules, and technological advancements will optimize waste management in naval institutions, reducing environmental impact while improving regulatory compliance and operational efficiency.